Dielectrical and Electrical Properties of Polystyrene films Doped with Copper Sulfate - Hussein Neama Najeeb (University of Thi-Qar Journal of Science, 2019)
The electrical characteristics of polystyrene doped with different concentrations (0,1,2,3,and 4wt%) of Copper Sulfate CuSO4.5H2O powder were studied . The films are prepared using solution casting technique, in order to investigate the effect of Copper Sulfate CuSO4.5H2O additions on the electrical properties of PS host. The D.C conductivity measured by measuring the D.C electrical resistance using the( Keithly Electrometer type 616C), and for different temperatures ranging from (30 – 80)oC . The dielectric properties measured by measuring the capacitor and the loss angle tangent as a function to the alternating electric field frequency using the (Agilent impedance analyzer 4294A), within the frequency range (50 – 6 ×106) Hz at room temperature. The experimental results showed that the dielectric constant is decrease with increase frequency of applied electrical field and increase with increasing concentrations, dielectric loss is decrease with increasing frequency of applied electrical field to be 0.5 MHz after this it was increasing , A.C electrical conductivity are increasing with increasing frequency of applied electrical field ,also, the results showed that the D.C electrical conductivity are increasing with increase concentration of PS and temperature, activation energy are decreasing with increase concentration of additive salt